Financial Analysis of Intensive Kamang Duck Farming Through R/C Ratio Analysis - Harly, Resolinda; Dwi Triani, Hera; Amri, Muhammad; Yanti, Gusri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The Kamang Duck is a local livestock breed from West Sumatra, originating from the Kamang region in West Sumatra. Kamang ducks can produce quality eggs and tender meat, contributing to Indonesia's food security. Duck farming is one of the livestock sectors with significant development potential, especially in Indonesia, where poultry meat consumption is high. To optimize farming ventures, financial analysis is a crucial aspect for evaluating profitability, efficiency, and business to develop duck farming. The research was conducted at Dapur Bundo N-3 in Nagari Kamang, Agam Regency, using a survey method presented descriptively in tables and figures. The study aims to determine the financial value of Kamang duck farming by analyzing costs, revenues, income, and the R/C ratio. The R/C ratio result of 1.53 indicates that, with a value greater than 1, this meat duck farming business is feasible. A hybrid duck farming business with an R/C ratio over 1 is suitable for further development. The BEP (Break-Even Point) production value of 72.06 kg indicates the level of production at which the meat duck farming operation breaks even, with no profit or loss. This is a crucial metric for understanding the minimum production required to sustain the business. The study's actual production of meat ducks was 130 kg. The research conducted at Dapur Bundo N-3 on the Kamang duck business, with a stock of 100 ducks and a rearing period of seven (7) weeks from DOD (Day-Old Ducks), yielded the following results: total rearing cost of Rp 3,817,473, total revenue of Rp 5,850,000, and profit of Rp 2,032,527. The Kamang broiler duck farming business, on a scale of 100 ducks, is considered viable, with an R/C ratio of 1.53.